A new perspective on the maternal mortality disparity. Issue 1 (12th September 2021) - Murphy, Laura; Liu, Fuqin
Abstract: The disparity in maternal mortality rates between ethnicities in the United States is alarming, with Black women at far higher risk of dying than women of other ethnicities. Factors typically thought of as protective in health disparity research are not necessarily protective with maternal mortality. Building upon a social justice framework by utilizing a strength‐based focus is needed when addressing this issue to build upon strengths and empower Black women as a part of the solution.